Rancang bangun mesin pengering buah pinang tipe rotari dengan sumber panas api kompor berbahan bahar oli bekas - Iman Iman Syahrizal; Irma Fahrizal Butsi Ningsih; Kurniawan Kurniawan (Universitas Muhammadiyah Metro, 2023)
This study aims to describe the working system and test the performance of the machine, to find out an overview of reducing the moisture content of betel nut dried with a rotary type betel nut dryer machine with a heat source from a used oil-fueled stove fire. The methods used in the study consist of the design stage and the performance test stage. The design stage was to carry out the construction design process, material selection, and fabrication process. While the performance test stage aims to determine the ability of the machine to carry out the betel nut drying process. The results of the design of the rotary type betel nut dryer machine consist of a heating system and a drive system. The heating system uses heat from the used oil-fueled stove and the drive system uses an electric motor connected to the reducer gearbox to rotate the cylinder of the drying chamber. The maximum air temperature generated during the 7-hour performance test process was 108oC with an air flow speed of 3,8 m/s. The results of the design of the drying machine are able to reduce fruit mass by 5.5 kg with a drying rate of 0.785 kg / hour on wet betel nut. The reduction in the moisture content of dried betel nut is directly proportional to the reduction in mass. During the 7-hour drying process, the moisture content of the betel nut is reduced by 55% with a reduction rate of 7.85% / hour